2022
DOI: 10.1111/aogs.14309
|View full text |Cite
|
Sign up to set email alerts
|

A force‐measuring device combined with ultrasound‐based elastography for assessment of the uterine cervix

Abstract: Introduction In this feasibility study, we hypothesize that the evaluation of cervical biomechanical strength can be improved if cervical length measurement is supplemented with quantitative elastography, which is a technique based on conventional ultrasound elastography combined with a force‐measuring device. Our aims were to: (a) develop a force‐measuring device; (b) introduce a cervical elastography index (CEI) and a cervical strength index (CSI; defined as cervical length × CEI); (c) evaluate how these ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 28 publications
0
1
0
Order By: Relevance
“…[ 19 , 20 ] Second, addition of multiple markers of cervical morphometry with, by example, elastography holds promise to evaluate critical features of antepartum cervix remodeling. [ 21 ] A third approach, distinct from sonography, is Raman spectroscopy for in vivo interrogation of the ectocervix. [ 22 ] This method can create a unique fingerprint of specific molecules during a routine exam which assesses specific biomolecular structure, concentrations, and water content — factors known to change during cervical remodeling.…”
Section: Alternative Approaches To Pre-induction Cervical Evaluationmentioning
confidence: 99%
“…[ 19 , 20 ] Second, addition of multiple markers of cervical morphometry with, by example, elastography holds promise to evaluate critical features of antepartum cervix remodeling. [ 21 ] A third approach, distinct from sonography, is Raman spectroscopy for in vivo interrogation of the ectocervix. [ 22 ] This method can create a unique fingerprint of specific molecules during a routine exam which assesses specific biomolecular structure, concentrations, and water content — factors known to change during cervical remodeling.…”
Section: Alternative Approaches To Pre-induction Cervical Evaluationmentioning
confidence: 99%
“…Various approaches have been reported in the literature to improve the application of USE in obstetrics. Studies have shown that SE can qualitatively detect the elasticity of the cervix when using reference materials, but the application of this technique in cervical disease has not been studied [ 80 ]. Hamza et al sought to combine lower uterine segment (LUS) thickness and SE to predict successful IOL within 24 h and intervals to onset of labor.…”
Section: Predicting Preterm Deliverymentioning
confidence: 99%